The concept of God in the Pavel Florensky metaphysics of all-unity - Kroczak, Justyna (Hybris, 2013)
Pavel Florensky is well-know Russian religious philosopher, famous above all for his works on orthodox icon, though his thought is considerably more extensive as it contains original reflections on theology, philosophy, philology and natural science. God was situated in the centre of all his deliberations. Therefore the theme of an article seems to be well-founded. I divided my analysis into three parts according to three fields of Florensky’s interests: orthodox christianity, sophiology and Greek philosophy. I will focus my attention on each of them respectively and then try to answer what Florensky understood by the term of God.